Sara Togo - Cinzana, Mali - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
This video describes the work of the research station in Cinzana where they select different crop varieties, test them and then give them to farmers to test their adaptability, productivity and resistance to different deseases.